2012
DOI: 10.1007/s11356-012-0968-z
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanoic acid (PFOA) acts as a tumor promoter on Syrian hamster embryo (SHE) cells

Abstract: Perfluorooctane sulfonate (PFOS) (C(8)F(17)SO(3)) and perfluorooctanoic acid (PFOA) (C(8)HF(15)O(2)) are synthetic chemicals widely used in industrial applications for their hydrophobic and oleophobic properties. They are persistent, bioaccumulative, and toxic to mammalian species. Their widespread distribution on earth and contamination of human serum raised concerns about long-term side effects. They are suspected to be carcinogenic through a nongenotoxic mode of action, a mechanism supported by recent findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 57 publications
1
9
0
1
Order By: Relevance
“…PFOA is widely used in the industrial production. It has been demonstrated that exposure to PFOA causes a variety of toxicities, including hepatotoxicity, carcinogenicity, neurotoxicity, immunotoxicity, and genotoxicity [24][25][26][27][28]. Epidemiologic studies have also shown that PFOA exposure is positively associated with cardiovascular disease [29], chronic kidney disease [30], thyroid disease [31], and hepatocellular damage [32].…”
Section: Discussionmentioning
confidence: 99%
“…PFOA is widely used in the industrial production. It has been demonstrated that exposure to PFOA causes a variety of toxicities, including hepatotoxicity, carcinogenicity, neurotoxicity, immunotoxicity, and genotoxicity [24][25][26][27][28]. Epidemiologic studies have also shown that PFOA exposure is positively associated with cardiovascular disease [29], chronic kidney disease [30], thyroid disease [31], and hepatocellular damage [32].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained for PFNA when tested at 0.125 or 0.25 mg/mL 95 . Exposure to PFOA at concentrations up to 300 µM for 5 or 24 hours did not induce DNA damage in Syrian hamster embryo cells as measured using the comet assay 96 . Negative results were also reported for the comet assay when freshly isolated Wistar rat testicular cells were exposed to 100 or 300 µM PFOA for 24 hours; however, a significant increase in DNA damage was observed when testicular cells were exposed to 300 µM PFNA for 24 hours 97 .…”
Section: Genetic Toxicitymentioning
confidence: 94%
“…PFOA did not induce mutations in bacteria (Fernández Freire et al., ; Buhrke et al., ), but increased mutation frequency at CD59 loci in human hamster hybrid cells at the highest applied (cytotoxic) concentration after long‐term (16 days) incubation (Zhao et al., ). Four studies reported no genotoxic effects (DNA strand breaks, micronuclei) after PFOA treatment in HepG2 (Florentin et al., ; Eriksen et al., ), V79 (Buhrke et al., ) and SHE cells (Jacquet et al., ). Three studies reported increased micronuclei, strand breaks and 8OHdG in HepG2 (Yao and Zhong, ; Wielsøe et al., ) and TK6 cells (Yahia et al., ).…”
Section: Assessmentmentioning
confidence: 99%